ANALISIS SISTEM INFORMASI AKUNTANSI ATAS SIKLUS PENGGAJIAN PADA PERUSAHAAN EKSPEDISI PT. HADI WIRAWIJAYA UTAMA CABANG KETAPANG - B51111052, HERI ANTONIUS GULTOM (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Accounting payroll information system are function, organization, forms, notes, and report on payroll to employees who are paid monthly, which is coordinated in such a way to provide the financial information needed by management in order to simplify the management of the company. This research aimed to analyze the payroll accounting information system that imposed at PT. HADI WIRAWIJAYA UTAMA Ketapang. The subject used in this research is PT. HADI WIRAWIJAYA UTAMA Ketapang located in Kecamatan Delta Pawan by analyzing the information system on the payroll cycle and internal control of the company on that accounting payroll information system. The results showed that payroll information system that imposed at PT. HADI WIRAWIJAYA UTAMA Ketapang has been running well, but there are still parts that doubled on the other sections that are considered less efficient within the system. Key Word: Payroll, Internal Control, Accounting Information Systems